Mike Meyers' CompTIA Security+ Certification Passport (Exam SY0-601) - Dunkerley, Dawn; Meyers, Mike 1961- (McGraw-Hill Education, 2021)
Inside this study guide, you'll find practice questions and content review, exam tips, updated information on real-world cyberattacks, and enhanced coverage of emerging topics.